Physicochemical characterization and oxidative stability of fish oil-loaded electrosprayed capsules: Combined use of whey protein and carbohydrates as wall materials. (August 2018) - García-Moreno, Pedro J.; Pelayo, Andres; Yu, Sen; Busolo, María; Lagaron, Jose M.; Chronakis, Ioannis S.; Jacobsen, Charlotte
Abstract: The encapsulation of fish oil in electrosprayed capsules using whey protein and carbohydrates (pullulan and dextran or glucose syrup) mixtures as glassy wall materials was studied. Capsules with fish oil emulsified by using only a rotor-stator emulsification exhibited higher oxidative stability than capsules where the oil was emulsified by high-pressure homogenization. Moreover, glucose syrup capsules (with a peroxide value, PV, of 19.7 ± 4.4 meq/kg oil and a content of 1-penten-3-ol of 751.0 ± 69.8 ng/g oil) were less oxidized than dextran capsules after 21 days of storage at 20 °C (PV of 24.9 ± 0.4 meq/kg oil and 1-penten-3-ol of 1161.0 ± 222.0 ng/g oil). This finding may be attributed to differences in oxygen permeability between both types of capsules. These results indicated the potential of both combinations of whey protein, pullulan, and dextran or glucose syrup as shell materials for the encapsulation of omega-3 PUFA in nano-microcapsules obtained by electrospraying. Graphical abstract: Image 1 Highlights: Fish oil-loaded nano-microcapsules were produced by electrospraying. Whey protein, pullulan and dextran or glucose syrup were used as wall materials. Rotor-stator emulsification led to capsules with higher oxidative stability. The glucose syrup matrix prevented more efficiently oxidation of encapsulated oil. Electrosprayed capsules are promising omega-3 nano-delivery systems.